Influence of Servant Leadership on Church Transformation - Simbolon, Guru Sozuaon; Sandroto, Christine Winstinindah (Institut Agama Kristen Negeri Toraja, 2025)
Church leadership is a strategic factor that determines the church's transformation toward growth, spiritual health, and the sustainability of church ministry. Of the many leadership styles, servant leadership is the most relevant to apply. This study aims to analyse the influence of servant leadership on church transformation. This study integrates servant leadership theory toward church transformation with biblical leadership narratives of Jesus, Paul, and Ezra. This study uses a descriptive, qualitative approach, drawing on a literature review of scientific journals, classic and contemporary leadership books, and biblical literature on spiritual leadership. Data analysis was conducted through the stages of data reduction, theme presentation, and argumentative synthesis. The research results show that servant leadership influences church transformation. The implications can be learned from the ministries of Ezra, Jesus, and Paul. Churches that learn from Ezra demonstrate spiritual renewal. Churches that imitate Jesus demonstrate social service and humility that transform communities. Churches that emulate Paul demonstrate the empowerment of a multiplicity of leaders. Thus, servant leadership is the driving force for church transformation.